Critiquing the Supreme Court of Kenya’s Jurisdictional Decisions to Listen to Matters of General Public Importance (Strathmore Law Review, 2023)
The Supreme Court of Kenya, as per Article 163 (4) (b), has the appellate jurisdiction to listen to appeals from the Court of Appeal that have been certified to be matters of general public importance. In Hermanus Phillipus Steyn v Giovanni Gnnechi-Ruscone, the Supreme Court put forth the Hermanus test that aimed at demystifying the concept of matters of general public importance. The prevailing understanding at the Supreme Court seems to take public interest to be an idea that is homogenous, applying to the country as a whole, ignoring the vast diversity in society. Hence, through the Hermanus test, the Supreme Court narrowly interprets its appellate jurisdiction to listen to matters of general public importance, going against transformative constitutionalism. This article aims to prove, through Court decisions, that the current interpretation of the ‘public interest’ in the Hermanus test goes against the purposive interpretation expected by the Constitution and access to justice. The article proposes reformulations to the Hermanus test that would meet the transformative aspect of the Constitution and fulfil the visions espoused by the constitution’s drafters.